Quasi-professional educational environment in the professional training of future teachers - Alieksieieva, Hanna; Petukhova, Liubov; Nesterenko, Maryna; Petryk, Kristina; Bernatova, Renata (Anadolu University, 2023)
During the distance education process caused by COVID-19, students do not have sufficient opportunity to do pedagogical practice, which requires strengthening their practice-oriented component of learning in other forms. This article substantiates the relevance of quasi-professional educational environment in the system of professional training of future teachers, which implies the creating conditions at the university as close as possible to the realities of the teacher’s work. The conditions which allowed to improve the graduates’ readiness to do their professional duties were developed and experimentally proven. The peculiarities of quasi-professional tasks based on imitation of real work situations, where student has no rules or samples for the completing, are revealed. In this way, they independently develop ossible models for their behavior in similar situations, based on theoretical and methodological knowledge and skills. The effectiveness of the author’s system of quasi-professional tasks aimed at the development of students’ pedagogical thinking and their mastery of the experience of modeling lessons is presented and examined. They are represented by three groups: didactic, methodological and technological, each of which has a specific purpose. It allows to cover all the spheres of professional development of higher education students: motivational, cognitive-operational and reflexive.
Keywords: Lesson modeling; practice-oriented learning; professional training of future teachers; quasiprofessional educational environment; quasi-professional tasks